Development of Word Game Algorithm for Learning Javanese Script - Ozzi Suria (Bina Nusantara University, 2018)
The students consider learning Javanese script to be difficult particularly in distinguishing and memorizing Carakan, and memorizing Sandangan and Pasangan with its writing rules. This work intends to develop a supporting medium for learning Javanese script. The development process is started by defining the game functionalities by using the use-case diagrams, and then, the activity diagram is created to describe the workflow of the game algorithm. The database to support the game is also created and displayed by using the physical data model. Afterward, the game algorithm script is created using JavaScript so that the game can be played through a web browser. There are 27 respondents requested to test the game and to fill in questionnaires about the web application. The results suggest that 100%of respondents agree that the web application is necessary and useful to learn Javanese script. The application provides positive benefit to the users such as students who still need to learn Javanese script in schools with 97% average success rate to run the game